Left Femoral Artery Occlusion due to Neglected Closed Fracture Distal Femur: A Case Report - Utomo, Pamudji; Siswanto, Totok (Indonesian Journal of Medicine, 2019)
Background: Distal femur fractures must always be considered for vascular disorders given the high risk. The incidence rate of femoral fractures is 1/10000 patients per year with the incidence rate of vascular injury around 0.10% -2.00%. Salter-Harris (SH) fracture classification is used in cases of fractures involving the growth plate (physeal plate) in children. Volkmann's ischemic contracture is caused by severe injury to the deep tissue and nerves. If tissue pressure is equal to or more than the perfusion pressure of the capillary, the microcirculation will be disrupted and ischemic occur. Normal myosit cells will be replaced by fibroblasts that tend to contract.Subjects and Method: A 10 years old boy had a traffic accident while riding a motorcycle 6 days before the patient came to the hospital. The patient could not walk, feeling pain and swelling on the left knee, the patient didn’t bring to the hospital immediately after the accident. On physical examination, there was angulation in the distal left femur, there was tenderness on palpation and unable to do dorsiflexion or moving the fingers of the left foot but still could feel touch stimulation on the pedis.Results: In our patient case with the diagnosis of left femoral artery occlusion et causa closed fracture distal femur (Salter-Harris type II) managed by surgery to release the femoral artery with internal fixation to the distal femur using Kirschner wire (minimally invasive) and massage to the femoral artery give optimal results.Conclusion: Surgery to release the femoral artery with internal fixation to the distal femur using Kirschner wire (minimally invasive) and massage to the femoral artery give an optimal result.Keywords: Salter-Harris fracture, femoral artery, Kirschner wire, Volkmann's ischaemic contractureCorrespondence: Pamudji Utomo. Department of Orthopaedics and Traumatology, Prof. Dr. R. Soeharso Orthopaedics Hospital. Email: utomodr@yahoo.comIndonesian Journal of Medicine (2019), 4(1): 75-81https://doi.org/10.26911/theijmed.2019.04.01.12